2022
DOI: 10.1007/s12355-022-01132-4
|View full text |Cite
|
Sign up to set email alerts
|

The Fiji Sugar Industry: Sustainability Challenges and the Way Forward

Abstract: This paper examines the problems facing the sugar industry in Fiji. It expands on the difficulties of world trade and the macro- and micro-problems that affects the sugar industry sternly. It also discusses local challenges associated with sugarcane crop production and sugar manufacturing in the country. Additionally, it provides an overview of some of the specific issues directly facing smallholder sugarcane growers. This study is based on a customised mixed-methods research conducted in the year 2015 in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Other studies have also reported that leaving sugarcane farming in the short term may not be economically feasible due to contractual obligations associated with land leases (Kurer, 2001;Singh, 2020;Dean, 2022). The majority of farmers remaining in the industry are planning to continue managing their farms without any plans to either expand or contract their growing areas.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Other studies have also reported that leaving sugarcane farming in the short term may not be economically feasible due to contractual obligations associated with land leases (Kurer, 2001;Singh, 2020;Dean, 2022). The majority of farmers remaining in the industry are planning to continue managing their farms without any plans to either expand or contract their growing areas.…”
Section: Discussionmentioning
confidence: 99%
“…The issues surrounding the sugarcane payment systems have also been documented. Farmers receive an average of 72% of the income distributed into several payments throughout the year, with the remaining 28% going to the mills (Dean, 2022). There are usually five payments spread over 18 months.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indigenous knowledge (IK) is a unique body of knowledge inherent to a particular society, group of people, or culture (Berkes, 2009; Dean, 2010, 2019). Although there exist distinctions in its usage, IK in the literature is commonly associated with and is used interchangeably with terms such as local knowledge, peoples’ knowledge, folk knowledge, traditional knowledge, Indigenous technical knowledge, fisherman’s knowledge, traditional ecological knowledge, traditional environmental knowledge, traditional science, or traditional wisdom, with overlapping definitions (Markkula et al, 2019).…”
Section: Introductionmentioning
confidence: 99%